Aplicação do fungo de degradação branca Pleurotus ostreatus (EB 016) na biorremediação do efluente da indústria de compensado - Heinz, Otto Lucas (2017)
The present work had the objective of characterizing the effluent from the Plywood Industry and evaluate the use of filamentous fungus Pleurotus ostreatus in the treatment in an air lift reactor, besides verifying the potentiality of the complementation of effluent treatment using a POA, Fenton type, in order to adjust it to the legal parameters to release it into water bodies in accord to the regulatory authorities. The brute effluent present 12.192 ± 100 mgO2L-1 of COD (Chemical Oxygen Demand), 8.849 ± 60 mgO2L-1 of BOD5,20 (Biochemical Oxygen Demand), 8.333 ± 30 color units, 1.220 ± 5 mgL-1 of total phenols and pH 4,63. The total solids content in the effluent was 18, 45 ± 0, 15 gL-1, in this total 2,73 ± 0,04 gL-1 corresponds to ashes, 1,36 ± 0,03 gL-1 soluble klason lignin and 49 ± 3 mgL-1 of insoluble klason lignin and approximately 71% toxicity expressed as inhibition to E.coli. The FTIR spectrometry of the solids of the effluent, indicated bands in 3430-3440 cm-1, 2938 cm-1, 1603 cm-1, that could be attributed to groups O-H, C-H, C=C. The biological treatment using the fungus Pleurotus ostreatus was initially optimized in an orbital incubator (shaker) by factorial design (2³) that getting the best reactional conditions to COD reduction (pH 5,7 and sucrose concentration of 7,5 gL-1 and nitrate concentration of 4,0 gL-1), being estimated a reduction of 64% of COD of effluent in 10 days. The biological treatment after 40 days in optimized conditions in air lift was capable of remove 87 % of COD of the effluent, 92 % of the BOD5,20, 72 % of reduction of total phenols, 36 % of color removal and acute toxicity reduced. The spectrometric analysis by FTIR confirmed the biological degradation by the correspondent peak reduction in relation to the characteristic peaks. Despite the results of fungal treatment being quite significant, there was a need of a complementation of treatment using AOP Fenton type, showing a reduction of 99 % of COD, 92 % of phenols content and 96 % effluents color. In this way, the bioremediation using the Pleurotus ostreatus combined with the Fenton process, presented promising results, in order to fit the majority of the parameters required by the legislation.